2015
DOI: 10.1152/ajprenal.00079.2014
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of neutral sphingomyelinase in the angiotensin II signaling pathway

Abstract: The possibility that angiotensin II (ANG II) exerts its effects through the activation of neutral sphingomyelinase (nSMase) has not been tested in kidneys. The results of the present study provide evidence for the activity and expression of nSMase in rat kidneys. In isolated perfused rat kidney, ANG II-induced renal vasoconstriction was inhibited by GW4869, an inhibitor of nSMase. We used nSMase for investigating the signal transduction downstream of ceramide. nSMase constricted the renal vasculature. An inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…One previous study reported that increased level of vascular ceramide induced by AngII contributed to the pathogenesis of renal injury possibly through TXA2-mediated vasoconstriction [ 144 , 145 ]. Another study was also in line with this conclusion, showing that AngII/AT1 receptor/nSMase/ceramide-PLA2/TXA2 pathway contributed to the regulation of renal vasoconstriction [ 146 ]. In a model of type 2 diabetes, a TXA2 synthase inhibitor was beneficial in reducing glomerular lesion and proteinuria [ 147 ].…”
Section: Txa2 In Kidney Diseasessupporting
confidence: 55%
“…One previous study reported that increased level of vascular ceramide induced by AngII contributed to the pathogenesis of renal injury possibly through TXA2-mediated vasoconstriction [ 144 , 145 ]. Another study was also in line with this conclusion, showing that AngII/AT1 receptor/nSMase/ceramide-PLA2/TXA2 pathway contributed to the regulation of renal vasoconstriction [ 146 ]. In a model of type 2 diabetes, a TXA2 synthase inhibitor was beneficial in reducing glomerular lesion and proteinuria [ 147 ].…”
Section: Txa2 In Kidney Diseasessupporting
confidence: 55%
“…Enhanced angiotensin II signaling in carotid body chemoreceptors contributes to hyperpnea in HFREF (52). GW4869 prevents vasoconstriction induced by angiotensin II in rat kidneys (6). Thus, GW4869 may have inhibited angiotensin II signaling in carotid body chemoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, all VaD patients showed a higher trend of Cer under the influence of these 2 risk factors. This is important since increased Cer can contribute to vasoconstriction and ischaemic injury through increased levels of TXA2 release in the vasculature [52] . Increased Cer can also impair the activity of glycogen synthase 3 activity which may lead to some of the physiological changes observed in type 2 diabetes and VaD [53] .…”
Section: Discussionmentioning
confidence: 99%